On the Evolution of Universe Using Relativistic Cosmology - Vigneswaran Ramamoorthy (On the Evolution of Universe Using Relativistic Cosmology, 2021)
For the collided region of two gravitationally bound structures A and B, geodesic equation is derived using calculus of variations. With the help of geodesic equation derived for the collided region of A and B, a method to calculate any possible curvature of universe beyond observable flat universe is detailed. This relativistic method is used to describe a generic idea on the evolution of gravitationally bound structures and its effect on the evolution of universe. Using this idea, distribution of matter and antimatter in the universe, observed accelerating expansion of universe, cosmic inflation, and large-scale structure of present universe are explained.